Zooprophylaxis implementation as malaria control program in rural areas in Indonesia: a systematic review - Unicha, Mutiara Shinta Noviar; Nastiti, Niken Irfa; Purwanti, Eti; Murdiati, Dwi (BKM Public Health and Community Medicine, 2021)
Objective: This study aims to review whether zooprophylaxis could be an effective prevention program for malaria infection in rural areas, required for its general implementations in Indonesia. Method: The words 'Zooprophylaxis' and 'malaria control' were searched by four electronic databases like ProQuest, EBSCO, Cochrane, and Universitas Gadjah Mada Library database. Only relevant articles which met the eligibility criteria were included in this systematic review. Critical appraisal using PRISMA 2009 and CONSORT 2010 checklist were applied for a full review by contributed authors. Results: The total of 647 articles were screened, and only 15 relevant articles were included in this study. Along with the use of household insecticides, Zooprophylaxis had been implemented in Banyumas Regency in Indonesia and proved to reduce the Man Bitting Rate (MBR) from 1,426 to 0,046. Only types of vector that have zoo-antrophylic bionomic that this program can control. The closer area of vector breeding sites with livestock to settlements plays an important role in the program's success. Also, the ecological-geographical conditions and the proportion of livestock-size could give a protective effect vice versa. Conclusion: Zooprophylaxis could be used effectively as a prevention program for malaria infection in rural areas by considering several conditions and mosquito bionomics. Coupled with the use of spray insecticides for night outdoor activities and bed-net for indoors and the application of ecological modification with the One Health approach, these could increase its effectiveness as a malaria control program in rural areas in Indonesia.